2018
DOI: 10.1039/c8gc00144h
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented catalytic performance in amine syntheses via Pd/g-C3N4 catalyst-assisted transfer hydrogenation

Abstract: A Pd/g-C3N4 catalyst exhibited a superb performance in the transfer hydrogenation of nitro compounds to generate their corresponding primary and secondary amines with formic acid as the hydrogen donor in aqueous solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 53 publications
2
47
0
Order By: Relevance
“…The full survey of XPS spectrum (Figure e) displays that C, N, Cu and Cl elements presence in the material, which is also well accordance with the SEM‐EDAX (Figure d). The peak at 283.10 eV in C 1s is attributed to the surface adventitious carbon and other peak allocated at 286.8 eV is due to the sp 3 ‐hybridized carbon bonded with N‐C=N of polymeric graphitic g‐C 3 N 4 (Figure a) . For N 1s, four distinguished peaks were observed.…”
Section: Figurementioning
confidence: 96%
See 1 more Smart Citation
“…The full survey of XPS spectrum (Figure e) displays that C, N, Cu and Cl elements presence in the material, which is also well accordance with the SEM‐EDAX (Figure d). The peak at 283.10 eV in C 1s is attributed to the surface adventitious carbon and other peak allocated at 286.8 eV is due to the sp 3 ‐hybridized carbon bonded with N‐C=N of polymeric graphitic g‐C 3 N 4 (Figure a) . For N 1s, four distinguished peaks were observed.…”
Section: Figurementioning
confidence: 96%
“…For N 1s, four distinguished peaks were observed. The peak at 397.10 eV has assigned for the nitrogen (N−C‐N), like pyridinium‐nitrogen and peak corresponding to 398.6 eV is due to the nitrogen N‐(C) 3 (Figure b) …”
Section: Figurementioning
confidence: 99%
“…Cao and co-workers developed reductive amination of aldehydes with nitroarenes using formic acid as a transfer hydrogenation reagent and gold catalyst supported on rutile titania (Au/TiO 2 -R) under very mild conditions (80 • C, 1 bar) in water (Zhang et al, 2016). Li and co-workers accomplished reductive benzylation of nitrobenzene with formic acid over Pd on graphitic carbon nitride (g-C 3 N 4 ) catalyst at 100 • C, yet the substrate scope was not studied (Xu et al, 2018). Zhou and Zhang successfully performed reductive alkylation of nitro compounds with HCOOH over Co-N x catalyst (Zhou and Zhang, 2017) or Co nanoparticles embedded in mesoporous nitrogen-doped carbon (Jiang et al, 2017;Zhou et al, 2017b).…”
Section: Intermolecular Reductive Amination Of Aldehydes and Ketones mentioning
confidence: 99%
“…However, high H 2 pressure and elaborate experimental setup (e.g., 110°C, 5 MPa) were usually required. As an alternative to direct hydrogenation, transfer hydrogenation of nitroarenes with formic acid [38][39][40][41][42][43], alcohol [44][45][46] or hydrazine [47] has also attracted considerable attention because of the moderate reaction conditions and readily available hydrogen donors [48,49], which may be regarded as hydrogen carrier. Beller and co-workers [39,40] demonstrated that Fe 2 O 3 or Co 3 O 4 nanoparticles surrounded by nitrogen-doped graphene layers (denoted as Fe 2 O 3 /NGr@C or Co 3 O 4 /NGr@C) were active catalysts for the activation of formic acid in the transfer hydrogenation of nitroarenes to anilines.…”
Section: Introductionmentioning
confidence: 99%